Receptor-mediated effects of clonidine on need-induced 3% NaCl and water intake - Yada, M. M.; Paula, Patricia Maria de [UNESP]; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Camargo, LAA; Saad, W. A.; DeLuca, L. A. (Elsevier B.V., 1997)
Clonidine combined with adrenergic antagonists were injected in the medial septal area in order to characterize the type of receptors involved with its inhibitory effect on 3% NaCl and water intake of sodium-depleted (furosemide + 24 h of removal of ambient sodium) and 30-h water-deprived rats, respectively. The inhibitory effect of clonidine (20 nmol) on need-induced water intake was reduced 50% by an 80-nmol dose of either idazoxan, yohimbine or prazosin. The inhibitory effect of clonidine (30 nmol) on need-induced 3% NaCl intake was completely antagonized by idazoxan (80, 160 nmol), not altered by yohimbine (40-160 nmol), and partially potentiated (40 nmol) or inhibited (160 nmol) by prazosin. Propranolol did not alter the effects of clonidine on either water (80 nmol) or 3% NaCl (40-160 nmol) intake. The results suggest that the inhibitory effects of clonidine on 3% NaCl and water intake are mediated by different types of alpha2-adrenergic receptors. Copyright (C) 1997 Elsevier B.V.
Keywords: adrenergic receptors; clonidine; noradrenaline; salt intake; water intake; drinking